Entre cercas, barracos e manchetes: uma análise sobre o problema agrário na agenda da mídia do sudoeste do Paraná. - Botelho, Ronaldo Martins (2005)
On this research we have analyzed the agrarian problem of press in the southwest of Paraná, in 2003. To give support to the research, we used two daily newspapers from Paraná: Jornal de Beltrão, from Francisco Beltrão and Diário do Povo, from Pato Branco, and two weekly newspapers, O Palmense and Correio Regional, both from Palmas. The theoretical empirical model adopted is the agenda setting, a hypotheses that holds that media participates in the construction and definition of people s choices. We have focused on this method the agenda of the media, aiming at noticing, though it, the elaboration of the micro social agrarian agenda. The procedures include, besides library research, the quantitative content analysis of these newspapers, and some interviews with editors and leaders in the area. The research presents some relevant topics as well. The agrarian theme involves, above all, the historical perception of the importance of the land and of the rural sector in the political-economical tradition of the country, as well as the fact that it is a permanent social problem. Considering a political perspective, the year of 2003 marks the beginning of a new government, with President Lula, whose proposals indicated sensitive changes in the policies for the land sector. Finally, in the academic-empirical dimension, we found that there is not enough study on agenda setting in this region, specially those related to the agrarian theme, even though this is a geographic area marked by historical land conflicts. In general, we have observed that the local newspapers are legitimating and act in mutual level, producing and exaggerating versions that are set by interest groups, which quite often reverberate in the press. Through the analysis of the graphs and of specific books, we noticed that the history of agents and media professionals; the class appeals that mobilize the actors and the level of dependence in the relations of native press with official government influence the local agenda. We have also identified that this determination occurs substantially through the editorial process, be it under the connivance of political power, or through the prerogative of the financial power. We have also noticed the relations between the mobility of the actors and the visibility of the agrarian theme in the micro regional press, through fields like tradition, family, status and publicity.